Camelid and shark single domain antibodies: structural features and therapeutic potential. (August 2017) - Könning, Doreen; Zielonka, Stefan; Grzeschik, Julius; Empting, Martin; Valldorf, Bernhard; Krah, Simon; Schröter, Christian; Sellmann, Carolin; Hock, Björn; Kolmar, Harald
Highlights: Camelids and sharks comprise heavy chain-only antibodies devoid of light chains. Their variable domains are able to address cryptic and recessed epitopes. These variable domains possess beneficial physicochemical properties. Several of these antibody domains are currently under investigation in the clinic. Abstract : In addition to canonical antibodies composed of heavy and light chains, the adaptive immune systems of camelids and cartilaginous fish comprise heavy-chain only isotypes (HcAb) devoid of light chains, where antigen-binding is mediated exclusively by one variable domain. Due to their inherent favorable attributes, such as high affinity and specificity for their cognate antigen, extraordinary stability, small size and, most importantly, the possibility to complement classical antibodies in terms of 'drugable' target-space, HcAb-derived entities evolved as promising candidates for biomedical applications of which many have already proven to be successful in early stage clinical trials.